Cardiovascular risk and prevention in patients with head and neck cancer treated with radiotherapy. Issue 3 (29th December 2016) - Okoye, Christian C.; Bucher, Jessica; Tatsuoka, Curtis; Parikh, Sahil A.; Oliveira, Guilherme H.; Gibson, Michael K.; Machtay, Mitchell; Yao, Min; Zender, Chad A.; Dorth, Jennifer A.
Abstract: Background: The underlying contributors to cardiovascular disease (CVD) in patients with head and neck squamous cell carcinoma (HNSCC) are poorly characterized. Methods: Patients with HNSCC who underwent definitive or adjuvant (chemo)radiation between 2011 and 2013 were retrospectively reviewed. The 10‐year risk estimates for a CVD event were calculated according to the Framingham Risk Score (FRS). Results: One hundred fifteen patients with predominantly stage III/IV HNSCC had a median follow‐up of 2 years. At diagnosis, 23% of patients had CVD. The FRS was higher among patients with laryngeal cancer versus other sites (20.5% vs 14.4%). Twenty‐four percent of all patients had uncontrolled blood pressure at diagnosis. Among the patients with CVD, 41% were not taking antiplatelet therapy and 30% were not taking statin therapy. Thirty‐four percent of patients without CVD had indications for initiating statin therapy. Conclusion: Patients with HNSCC have a high baseline CVD risk and many do not receive optimal preventive care. © 2016 Wiley Periodicals, Inc. Head Neck 39: 527–532, 2017